The Impact of Visual e-WOM on Tourists’ Information Searches Related to HORECA Services - Melanthiou, Yioula; Kfoury, Jessy; Papasolomou, Ioanna (My University, 2024)
This study examines how customer booking intentions in the HORECA industry are affected by visual electronic word of mouth (eWOM) published on Instagram. Data from 300 international travelers, from both Generation Y and Generation Z, was gathered with emphasis on factors such as information quality, information credibility, website quality, motivation, innovativeness, destination fascination, popularity heuristics, destination image, and user-generated content. Using SPSS for statistical analysis, it was shown that these factors had a substantial impact on visual eWOM. Furthermore, visual eWOM appears to mediate directly and indirectly the association between these factors and consumer intentions, according to Hayes process macros analysis. Remarkably, disparities in the sense of destination appeal and believability were found between Generation Z and Generation Y. The study adds to theories like the theory of planned behavior and offers useful implications for marketers and legislator
Keywords: Visual eWOM; Consumer booking intentions; Information search; Social media; HORECA; Instagram; Consumer behavior